THE IMPORTANCE OF MOBILE LEARNING (M-LEARNING) ACTIVITIES TO ENHANCE STUDENTS’ LEARNING ENGAGEMENT IN INDONESIAN SECONDARY SCHOOLS - Dodi Widia Nanda (Dharmas Education Journal (DE_Journal), 2020)
Mobile technologies have been considered a valuable tool to enhance various learning practices. Therefore, this paper critically evaluates existed literature reviews in regard to the importance of the related learning tool to increase students’ learning engagement in Indonesian secondary schools. In particular, this paper attempts to examine how mobile learning activities provide more advantages instead of the disadvantages in the classroom. Furthermore, this research also discusses the possible challenges in the implementation of M-learning and evaluates M-learning activities in the learning process. Ultimately, the paper concludes that M-learning activities play essential roles to offer various benefits to students’ learning engagement in the Indonesian secondary school context. For instance, developing students’ personal development, triggering students to work collaboratively and providing flexible learning.